Chemical, thermal and economic aspects for the energy balance of coal gasification power plants with and without CO2 recovery - M. A. Ibrahim, Said; E.M Samy, Mostafa (International Journal of Engineering and Technology, 2018)
This paper presents a methodology for studying the chemical, thermal processes and economics for the gasification systems employed in coal fired power stations through thermodynamic analyses based on thermodynamic laws in order to gain some new aspects of the plant performance. A resourceful computer program is developed and designed to calculate all necessary design and performance data for four selected coal fired power plants for all coal ranks. Detailed manual calculations were performed for the results. Comparison of computer and manual results are in excellent agreement which indicates that the present program is an accurate quick powerful tool for all users. The main findings of this paper are that Integrated Coal Gasification Combined Power Generation Plants with CO2 recovery increase the plant's thermal efficiency and decrease the CO2 emission. The thermodynamics, hydrodynamics, and kinetics of each reaction to the gas combinations were most likely tested by each of the techniques when using a variety of fuels under the condition of "Oxygen gas at 30 bar pressure". The economic analysis is based on analyzing the economics of carbon dioxide capture and storage and the amount of carbon dioxide emitted from power plants. Finally, with new developments, the capture and sequestration of CO2 Â Â could lead to.Â Â